Non-Steroidal Anti-Inflammatory Drugs and Brain Inflammation: Effects on Microglial Functions - Maria Antonietta Ajmone-Cat; Antonietta Bernardo; Anita Greco; Luisa Minghetti (MDPI AG, 2010)
The term NSAID refers to structurally diverse chemical compounds that share the ability to inhibit the activity of the prostaglandin (PG) biosynthetic enzymes, the cyclooxygenase (COX) isoforms 1 and 2. The suppression of PG synthesis at sites of inflammation has been regarded as primarily responsible for the beneficial properties of NSAIDs, but several COX-independent effects have been described in recent years. Epidemiological studies indicate that NSAIDs are neuroprotective, although the mechanisms underlying their beneficial effect remain largely unknown. Microglial cells play a major role in brain inflammation and are often viewed as major contributors to the neurodegeneration. Therefore, microglia represent a likely target for NSAIDs within the brain. In the present review, we focused on the direct effects of NSAIDs and selective COX-2 inhibitors on microglial functions and discuss the potential efficacy in controlling brain inflammation.